An Ultra-Rapid Real-Time RT-PCR Method Using PCR1100 for Detecting Human Orthopneumovirus - Shirato, Kazuya; Nao, Naganori; Kawase, Miyuki; Kageyama, Tsutomu (Japanese Journal of Infectious Diseases, 2020)
Human orthopneumovirus, also known as the respiratory syncytial virus (RSV), is a leading cause of respiratory tract infections in children worldwide. The World Health Organization has taken steps toward establishing a global surveillance system for RSV, based on the global influenza surveillance and response system initiated in 2015. The US Centers for Disease Control and Prevention (CDC) has developed a genetic detection method based on real-time reverse transcription polymerase chain reaction (RT-PCR), which is used in global RSV surveillance. In Japan, immunoassay-based rapid antigen detection kits are widely used for the detection of RSV. In this study, an ultra-rapid real-time RT-PCR method for the rapid detection of RSV was developed using the PCR1100 device based on the US CDC assay in order to detect RSV in comparable time to rapid test kits. The ultra-rapid real-time RT-PCR could detect RSV viral RNA in less than 20 min while maintaining sensitivity and specificity comparable to conventional real-time RT-PCR using large installed instruments. Furthermore, combining ultra-rapid real-time RT-PCR with the M1 Sample Prep kit reduced the total working time for the detection of RSV from clinical specimen to less than 25 min, suggesting this method could be used for point-of-care RSV testing.